2021
DOI: 10.1101/2021.03.24.436814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ratio of cytotoxic lymphocytes to M2-like macrophages is prognostic in immunogenic tumors

Abstract: Immune cells in the microenvironment shape tumor development and progression. The prognostic value of T-cell-based immune scores exceeds those of clinical parameters in colon cancer, but reflects only a part of the anti-tumor immune response. Here, we assessed 15 distinct immune cell classes and identified a simple prognostic signature based on pro- and anti-tumoral immune cells in the tumor microenvironment. The ratio of cytotoxic lymphocytes to tumor supportive macrophages predicted survival better than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Tumor immune surveillance is a balance between immune cells that promote tumor progression (pro-tumorigenic cells) and cells that promote tumor rejection (anti-tumorigenic cells) (4). Studies in animal cancer models have shown that exercise shrinks tumors by enhancing the tumor infiltration of anti-tumorigenic cells, thus natural killer (NK) and cytotoxic T cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor immune surveillance is a balance between immune cells that promote tumor progression (pro-tumorigenic cells) and cells that promote tumor rejection (anti-tumorigenic cells) (4). Studies in animal cancer models have shown that exercise shrinks tumors by enhancing the tumor infiltration of anti-tumorigenic cells, thus natural killer (NK) and cytotoxic T cells (5,6).…”
Section: Introductionmentioning
confidence: 99%